iTRAQ-based quantitative proteomic analysis of herbicide stress in Avena ludoviciana Durieu - Hossein Adim; Leila Fahmideh; Barat Ali Fakheri; Hamid Najafi Zarrini; Hamidreza Sasanfar (Scientific Reports)
Abstract Winter wild oat (Avena sterilis subsp. ludoviciana (Durieu) Gillet & Magne) has been considered the most common and troublesome weed in wheat fields of Iran. The widespread and continuous use of herbicides has led to the emergence and development of resistant biotypes in A. ludoviciana, making it one of the most important herbicide-resistant weeds within field crops. Considering the importance of understanding the mechanisms underlying resistance to herbicides and identifying key proteins involved in the response to Acetyl-coenzyme A carboxylase (ACCase) and Acetolactate synthase (ALS) inhibitor herbicides in A. ludoviciana. This study aimed to identify the proteins involved in herbicide resistance in A. ludoviciana using the Isobaric Tags for Relative and Absolute Quantification (iTRAQ) technique. In this study, a total of 18,313 peptides were identified with ≤ 0.01 FDR, which could be classified into 484 protein groups. Additionally, 138 differentially expressed proteins (DEPs) were identified in the resistant biotype (R), while 93 DEPs were identified in the susceptible biotype (S). Gene Ontology (GO) analysis revealed that these DEPs mainly consisted of proteins related to photosynthesis, respiration, amino acid synthesis and translation, secondary metabolite biosynthesis, defense proteins, and detoxification. Furthermore, enrichment pathway analysis using Kyoto Encyclopedia of Genes and Genomes (KEGG) showed that the most important pathways included metabolic pathways, carbohydrate metabolism, secondary metabolites, amino acid synthesis, and photosynthesis. The function of DEPs indicated that some proteins, such as cytochrome P450, play a direct role in herbicide detoxification. Overall, the results of this study demonstrated the complex response of the resistant biotype to herbicides and its ability to increase antioxidant capacity through up-regulated detoxification proteins, particularly cytochrome P450 (Q6YSB4), and defense proteins, particularly superoxide dismutase (Q0DRV6) and polyamine oxidase (Q7XR46). In the resistant A. ludoviciana populations, in addition to the activation of enzymatic and non-enzymatic defense systems, other strategies such as reduced photosynthesis and respiration, increased transcription and translation activity, enhanced lipid metabolism, regulation of cellular processes and homeostasis, and up-regulation of proteins associated with signaling and ion channels play a role in resistance to herbicide. Overall these findings provide new insights into the role of different proteins in resistance to herbicides and contribute to a comprehensive understanding of herbicide resistance in A. ludoviciana.